STUDI KOMPARASI MODEL PEMBELAJARAN STAD DAN NHT TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROLISIS GARAM - nais wulandari; lazulva lazulva (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
AbstractThis research was instigated by the implementation of chemistry learning that needed student-centered learning interactions by implementing Student Teams Achievement Division (STAD) and Numbered Heads Together (NHT) types of cooperative learning.  This research aimed at knowing the difference on learning achievement between students taught by using STAD model and those who were taught by using NHT model on Salt Hydrolysis lesson.  The eleventh-grade students of Natural Science at State Senior High School 1 Pasir Penyu in the Academic Year of 2018/2019 were the population of this research.  Purposive sampling technique was used in this research, and there were 33 students as the samples in experiment 1 and experiment 2 groups.  The research findings showed that the increase of learning achievement of students taught by using STAD model was 18.06, and the mean increase of learning achievement of students taught by using NHT model was 14.60.  Besides, based on the statistical analysis, it was obtained that there was a difference on learning achievement between students taught by using STAD model and those who were taught by using NHT model on Salt Hydrolysis lessonat State Senior High School 1 Pasir Penyu, tobserved was higher than ttable (2.063>1.997) and the score of sig was lower than 0.05, so H0 was rejected..Keywords: NHT, Salt Hydrolysis, STAD